2000
DOI: 10.1021/ie0003436
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Gasification in Supercritical Water

Abstract: Biomass feedstocks, including corn- and potato-starch gels, wood sawdust suspended in a cornstarch gel, and potato wastes, were delivered to three different tubular flow reactors by means of a “cement” pump. When rapidly heated to temperatures above 650 °C at pressures above the critical pressure of water (22 MPa), the organic content of these feedstocks vaporized. A packed bed of carbon within the reactor catalyzed the gasification of these organic vapors in the water; consequently, the water effluent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
276
0
14

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(293 citation statements)
references
References 57 publications
3
276
0
14
Order By: Relevance
“…Typical catalyst supports, e.g., silica and γ-alumina, cannot be used, as they will be severely degraded under the harsh conditions of the supercritical water. During the last 15 years, new catalyst formulations have been developed that use combinations of stable metals such as ruthenium (Ru), or nickel (Ni) bimetallics, and stable supports such as titania, zirconia, or carbon (Elliott et al 2006;Antal et al 2000;Waldner et al 2007;Peterson et al 2008;Vogel 2009). …”
Section: Hydrothermal Gasificationmentioning
confidence: 99%
“…Typical catalyst supports, e.g., silica and γ-alumina, cannot be used, as they will be severely degraded under the harsh conditions of the supercritical water. During the last 15 years, new catalyst formulations have been developed that use combinations of stable metals such as ruthenium (Ru), or nickel (Ni) bimetallics, and stable supports such as titania, zirconia, or carbon (Elliott et al 2006;Antal et al 2000;Waldner et al 2007;Peterson et al 2008;Vogel 2009). …”
Section: Hydrothermal Gasificationmentioning
confidence: 99%
“…Morimoto et al [13] of Kyoto University studied hydrothermal gasification process of brown coal. Antal et al [14] reported the gasification of cornstarch and wood dust. Yoshida et al [15] studied supercritical water gasification of cellulose, hemi-cellulose, and lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Longer residence time can improve gasification thoroughness, but there is also an inverse relationship between temperature and reaction completeness, dropping from a few minutes below 600°C to a few seconds above 600°C. The optimal temperature threshold for SCWG (i.e., 600°C) has been shown on the lower side of the conversion range for higher concentration biomass in the absence of a catalyst [23][24][25][26]. From the viewpoint of thermodynamics, biomass can be gasified completely in SCW with a product formation of H 2 and CO 2 , but adequate reaction time was required to complete the gasification process.…”
Section: Effect Of Residence Timementioning
confidence: 99%